Creation of a Long-Acting Nanoformulated 2′, 3′-Dideoxy-3′-Thiacytidine. (1st March 2017) - Guo, Dongwei; Zhou, Tian; Araínga, Mariluz; Palandri, Diana; Gautam, Nagsen; Bronich, Tatiana; Alnouti, Yazen; McMillan, JoEllyn; Edagwa, Benson; Gendelman, Howard E.
Abstract : Background: Antiretroviral drug discovery and formulation design will facilitate viral clearance in infectious reservoirs. Although progress has been realized for selected hydrophobic integrase and nonnucleoside reverse transcriptase inhibitors, limited success has been seen to date with hydrophilic nucleosides. To overcome these limitations, hydrophobic long-acting drug nanoparticles were created for the commonly used nucleoside reverse transcriptase inhibitor, lamivudine (2′, 3′-dideoxy-3′-thiacytidine, 3TC). Methods: A 2-step synthesis created a slow-release long-acting hydrophobic 3TC. Conjugation of 3TC to a fatty acid created a myristoylated prodrug which was encased into a folate-decorated poloxamer 407. Both in vitro antiretroviral efficacy in human monocyte-derived macrophages and pharmacokinetic profiles in mice were evaluated for the decorated nanoformulated drug. Results: A stable drug formulation was produced by poloxamer encasement that improved monocyte–macrophage uptake, antiretroviral activities, and drug pharmacokinetic profiles over native drug formulations. Conclusions: Sustained release of long-acting antiretroviral therapy is a new therapeutic frontier for HIV/AIDS. 3TC depot formation in monocyte-derived macrophages can be facilitated through stable subcellular internalization and slow drug release. Abstract : Supplemental Digital Content is Available in the Text.